Effect of Microclimate Temperature and Relative Humidity on the Postharvest Quality of Coconut Sap and Sugar - Sri Rahayoe; Hilda Maya Sintia Dewi; Andri Prima Nugroho; Arifin Dwi Saputro; Ngadisih Ngadisih (The University of Lampung, 2025)
Coconut sap, increasingly recognized as a functional sweetener, is highly perishable and influenced by environmental conditions during postharvest handling, yet the specific impacts of microclimatic variables such as temperature and relative humidity (RH) on sap and sugar quality remain inadequately studied. This research investigates the effects of RH and temperature on key physicochemical parameters of coconut sap—pH, Brix, and density—and evaluates their influence on coconut sugar quality, focusing on moisture, ash content, and color. Sap was collected biweekly in Central Java over a five-week period and analyzed in conjunction with environmental data recorded using an IoT-based weather station. Increased RH was significantly associated with decreased sap pH (r = –0.482, p = 0.007) and showed a weak negative correlation with Brix. Density remained stable across varying RH levels. Although temperature showed visual trends in sap quality parameters, statistical analysis did not reveal significant correlations, likely due to the narrow temperature range during the observation period. Throughout sugar processing, TSS increased consistently across boiling, saturation, and oversaturation stages. Final sugar blocks maintained stable moisture (6–8%) and ash content (1.8–2.2%), with color variations reflecting Maillard and caramelization reactions. Maintaining RH below 85% is recommended to preserve sap quality and product consistency. Keywords: Coconut sap, Coconut sugar, Postharvest quality, Relative humidity, Temperature.